Strategic plan for Airwolf Aviation Corporation - Sambalod, Josie M.; Ellson, Adela G.; Pabularcon, Liza N. (Davao City School of Management, University of the Philippines Mindanao, 2007)
This strategic plan provides the basis for Airwolf Aviation Corporation (AWAC's) strategic direction setting and business performance management. The company was established in 1997 and its mission and corporate objectives summarize its corporate intent. AWAC's competitive advantage is the very high barrier to entry into the industry. This includes some of the factors like high capitalization business and the need of technically skilled workforce. For the past nine years of operation, AWAC showed a considerable reputation to its customers and still counting for more years of providing aerial spray to banana plantations in Davao Region. Since its inception, AWAC has been managed by a professional pilot as the general manager. Its organization has been established and the business has been run to what as they believe is the right thing. Its customers come in and get contracted them for their services. Together with the expansion of its customers, the company grows and operates in full capacity. However, as the organization grows older, organization develops, workforce become more diverse, technology improves and competition heightens, the traditional way of management became antiquated. This paper aims to develop a strategic plan for AWAC based on the abovementioned facts. Some of the highlights include an assessment of its strategic opportunities and threats together with its strengths and weaknesses. The long term strategic positioning of the company is analyzed and guided through the use of Strategic Management Framework by Pearce and Robinson Strategic Management. The Quantitative Strategic Planning Matrix (QSPM) has been used in determining the grand strategy. Finding showed that the corporate strategy is based on three strategic platforms such as growing the business, leadership innovation and organizational effectiveness and joint venture. The grand strategy posited by QSPM is leadership innovation and organizational effectiveness. It is believed that, as organizations develop outstanding leadership such as transformational, charismatic and visionary has risen in importance. The driving framework that is used in the study is an adaptation from Densten and Gray Leadership Applications-Organizational Effectiveness paper. Based on Densten and Gray's analysis the said framework states that organization needs to be adaptable and flexible, but also stable and controlled. Furthermore, this plan sets out the high priority strategic initiatives that support these strategic platforms in accordance to the corporate objectives and is integrated to the company's key result areas. The KRA's includes on: safety and environment, operational excellence, customers and market development, employees, owners and other key stakeholders.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, April 2007.